Biomimetics Design of Sandwich-Structured Composites - Kunzmann, Carsten; Aliakbarpour, Hamaseh; Ramezani, Maziar (MDPI AG, 2023)
In the context of energy efficiency and resource scarcity, lightweight construction has gained significant importance. Composite materials, particularly sandwich structures, have emerged as a key area within this field, finding numerous applications in various industries. The exceptional strength-to-weight ratio and the stiffness-to-weight ratio of sandwich structures allow the reduction in mass in components and structures without compromising strength. Among the widely used core designs, the honeycomb pattern, inspired by bee nests, has been extensively employed in the aviation and aerospace industry due to its lightweight and high resistance. The hexagonal cells of the honeycomb structure provide a dense arrangement, enhancing stiffness while reducing weight. However, nature offers a multitude of other structures that have evolved over time and hold great potential for lightweight construction. This paper focuses on the development, modeling, simulation, and testing of lightweight sandwich composites inspired by biological models, following the principles of biomimetics. Initially, natural and resilient design templates are researched and abstracted to create finished core structures. Numerical analysis is then employed to evaluate the structural and mechanical performance of these structures. The most promising designs are subsequently fabricated using 3D printing technology and subjected to three-point bending tests. Carbon-fiber-reinforced nylon filament was used for printing the face sheets, while polylactic acid (PLA+) was used as the core material. A honeycomb-core composite is also simulated and tested for comparative purposes, as it represents an established design in the market. Key properties such as stiffness, load-bearing capacity, and flexibility are assessed to determine the potential of the new core geometries. Several designs demonstrated improved characteristics compared to the honeycomb design, with the developed structures exhibiting a 38% increase in stiffness and an 18% enhancement in maximum load-bearing capacity.
Keywords: 40 Engineering; 4016 Materials Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; 4016 Materials engineering